Sequential State-Parameter Estimation for Parabolic Problems Using Particle Filter with the Method of Fundamental Solutions - Kopperschmidt, Carlos Eduardo Polatschek (2020)
Thermal processes related to most of practical problems involve the need to be investigated as inverse problems. In this aspect, the implementation of numerical or analytical-numerical solutions is essential because of complexity in obtaining purely analy